ANALISIS UNSUR INTRINSIK DAN NILAI MORAL DALAM CERPEN “WANITA BERWAJAH PENYOK” KARYA RATIH KUMALA - Erlin Puspitasari Prasetyo (IKIP Siliwangi, 2020)
Ratih Kumala is a short story writer and novel who studies at Sebelas Maret University in the Faculty of English Literature, although his name is foreign, Ratih Kumala represented Indonesia at the 2019 Beijing International Book Fair (BIBF) which is the largest book exhibition in Asia. Researchers chose a short story titled